Digital design - Vahid, Frank (New Delhi Wiley, 2006)
While most popular digital design books present a perspective rooted in the 1970s and 1980s, Digital System Design takes the subject into the 21 st century. It quickly moves through the low-levels of design, making a clear distinction between design and gate-level minimization. The book also emphasizes how one of the key uses of digital design today is to build high-performance alternatives to software in addition to glue logic. And it swiftly progresses to register-transfer-level (RTL) design since that is the level at which most digital design in practice today is performed.